SLA-VER: study protocol description and preliminar results of the first italian RCT on conservative treatment of distal radial fractures - Maluta, Tommaso; Cengarle, Matteo; Dib, Giovanni; Bernasconi, Alice; Lavini, Franco; Ricci, Matteo; Vecchini, Eugenio; Samaila, Elena Manuela; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2019)
Introduction: There is no consensus on which is the best way to maintain initial reduction of a distal radius fractures (DRFs). The aim of this study is to test the hypothesis that below elbow cast (BEC) is equivalent to above elbow cast (AEC) in maintaining initial reduction of DRFs. This paper will report on midterm results. Methods: SLA-VER is a prospective, monocentric, randomized, parallel-group, open label, blinded endpoint evaluation non-inferiority trial (PROBE design) comparing the efficacy of AECs and BECs in DRFs conservative treatment in terms of loss of radial height (RH), radial inclination (RI) and volar tilt (VT) during cast immobilization (average 35 days) of 353 consecutive DRFs. Non-inferiority thresholds are 2 mm for radial height, 3Åã for radial inclination and 3Åã for volar tilt. Study population will be 353 patients, randomized into 2 groups (AEC vs BEC). One-hundred patients have completed the study so far. Results: Patients in BEC group lost 1,75 mm of RH, 2,9Åã of RI and 4,5Åã of VT over the course of cast immobilization. Patients in AEC group lost 1,71 mm of RH, 2,2Åã of RI and 4,8Åã of VT. Raw differences between average loss of RH, RI, VT during treatment between study groups were respectively 0,04 mm, 0,7Åã and 0,3Åã. Logistic and ANCOVA models have been used to correct for confouding variables. Conclusions: Difference of loss of RH, RI and VT between the two groups are all below the non inferiority thresholds. Cast type does not seem to affect maintenance of reduction in conservatively managed DRFs.